BENZIMIDAZOLE MOLECULE AS NEW ANTICANCER AGENT; DESIGN, SYNTHESIS AND ADMET PREDICTION - Rashid, Dr. Mohammad Rashid (Journal of the Chilean Chemical Society, 2021)
A new series of benzimidazole clubbed with oxadiazole ring with second amine (4a-l) were design and synthesize with an intention to search an anticancer lead compound under microwave irradiation in good yields. Further, the synthetic compounds were spectral characterization with modern instrumental techniques such as FTIR, NMR (1H and 13C), MS and elemental analysis. Anticancer activities of synthesized compounds were investigated at the National Cancer Institute (NCI) against NCI 60 cell line panel, results showed good to notable anticancer activity. With the help of molinspiration, drug like properties and bioactivity score for drug targets of synthetic compounds were predicted and found to obey the Lipinski’s rule, and result indicates that the derivatives are orally active molecules. Osiris property explorer was used for the prediction of drug relevant properties and toxicity of synthetic compounds. Pre ADMET and Lazar toxicity was also used to estimate the ADME and toxicity of the synthetic compounds. So that, these new hybrids compounds could serve as potential template to become leads in near future for the discovery and development of new effect orally drugs molecules. Two compounds, 4c [1-(1H-benzo[d]imidazol-2-yl)-3-(5-((4-methylpiperazin-1-yl)methyl)-1,3,4 -oxadiazol-2-yl) propan-1-one] and 4k [3-((5-(3-(1H-benzo[d]imidazol-2-yl) -3-oxopropyl)-1, 3, 4-oxadiazol-2-yl) methyl)-5-methylpyrimidine-2,4(1H, 3H)-dione] were exhibited highest drug score and emerged as lead compounds and motivates for further development of more effective and safer compounds.